2006
DOI: 10.1038/sj.npp.1301279
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of N-Desmethylclozapine as a Potential Antipsychotic—Preclinical Studies

Abstract: There is growing interest in N-desmethylclozapine (NDMC), the major metabolite of clozapine, as a unique antipsychotic because it acts in vitro as a 5-HT 2 antagonist and as a partial agonist to dopamine D 2 and muscarinic receptors. To explore this, we compared NDMC to a typical (haloperidol), atypical (clozapine), and partial-agonist atypical (aripiprazole) antipsychotic in preclinical models. The comparison was carried out using: brain D 2 and 5-HT 2 receptor occupancy; animal models predictive of antipsych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 57 publications
(65 reference statements)
2
25
0
Order By: Relevance
“…6). NDMC displays strong partial agonist activity at M 1 receptors (Davies et al 2005;Lameh et al 2007;Natesan et al 2007), and while CLZ has traditionally been considered to be a muscarinic antagonist, more recent work has shown that CLZ is a partial agonist at M 1 , M 2 , and M 3 receptors and is a full agonist at M 4 receptors (see Raedler et al 2007). Thus, CLZ and NDMC also appear to share similarities in terms of their activity at muscarinic receptors (which may or may not be related to their discriminative cue properties).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6). NDMC displays strong partial agonist activity at M 1 receptors (Davies et al 2005;Lameh et al 2007;Natesan et al 2007), and while CLZ has traditionally been considered to be a muscarinic antagonist, more recent work has shown that CLZ is a partial agonist at M 1 , M 2 , and M 3 receptors and is a full agonist at M 4 receptors (see Raedler et al 2007). Thus, CLZ and NDMC also appear to share similarities in terms of their activity at muscarinic receptors (which may or may not be related to their discriminative cue properties).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been increasing interest in the possibility that NDMC may be a novel APD because of its interesting in vitro receptor binding profile. Like CLZ, it is a potent 5-HT 2A antagonist, yet in contrast to CLZ, it is a partial agonist at DA D 2 (Lameh et al 2007;Natesan et al 2007) and at DA D 3 receptors (Burstein et al 2005;Novi et al 2007). It has been suggested that NDMC's unique muscarinic agonist properties may provide one molecular explanation for the superior clinical effects of CLZ (Weiner et al 2004) and may more effectively treat the cognitive deficits that are observed in schizophrenic patients (Li et al 2005).…”
mentioning
confidence: 99%
“…At the doses chosen in my experiment (1.3 mg/kg for risperidone, 15 mg/kg for clozapine and 0.05 mg/kg for haloperidol), this level of dopamine D2 receptor occupancy would appear to have been achieved Natesan et al 2007;Wadenberg et al 2001b). Higher rates of D2 receptor occupancy are associated with extra-pyramidal side-effects (Natesan et al 2007;2008;Natesan et al 2006a;Wadenberg et al 2001b). Here I showed that these doses of APDs disrupted avoidance response without inducing any significant increase in escape failures.…”
Section: Discussionmentioning
confidence: 81%
“…Although sensitization to risperidone in a CAR paradigm has also been reported in adult rats (Gao and Li 2013) (Natesan et al 2007). This suggests that no significant increase in behavioural sensitivity to haloperidol was induced at any ages after drug washout.…”
Section: Behaviour After a Drug-free Intervalmentioning
confidence: 96%
See 1 more Smart Citation